Cell enumeration and visualisation by transmission electron microscopy of Lactobacillus rhamnosus treated with cinnamon (Cinnamomum zeylanicum B.) essential oil - Feniman, C. M.; Rall, V. L. M. [UNESP]; Doyama, J. T. [UNESP]; Fernandes Junior, A. [UNESP] (Taylor & Francis Ltd, 2012)
The use of essential oils (EOs) in functional foods containing probiotic microorganisms must consider the antimicrobial activity of these oils against beneficial bacteria such as Lactobacillus rhamnosus. This study aimed to evaluate the sensitivity of L. rhamnosus cultures treated with cinnamon EO through viable cell counts and visualisation by transmission electron microscopy. Cinnamon EO at a concentration of 0.04% had a bacteriostatic activity after 2 h of incubation. Although slight alterations were detected in the cell structure, this concentration was considered to be bactericidal, since it led to a significant reduction in cell numbers after 24 h. on the other hand, cinnamon EO at a 1.00% concentration decreased cell counts by 3 log units after 2 h incubation and no viable cell count was detected after 24 h. Transmission electron microscopy indicated that cells treated with 1.00% cinnamon EO were severely damaged and presented cell membrane disruption and cytoplasmic leakage.
Keywords: essential oils; probiotic foods; Lactobacillus rhamnosus